2012
DOI: 10.1519/jsc.0b013e318245bde1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Anaerobic Threshold from Heart Rate Variability in an Incremental Swimming Test

Abstract: This study aimed to evaluate, in swimming, the agreement between the anaerobic threshold (AT) as determined from the analysis of blood lactate concentration ([La]) and from a new method based on the heart rate (HR) variability (HRV). Fourteen high-level swimmers completed an incremental 7 × 200-m front crawl test, during which the HRV was measured continuously and [La] was collected after each step. To individuate the AT, the trends of the high-frequency HRV spectral power (HFPOW) and of the fraction of HFPOW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 22 publications
6
50
0
6
Order By: Relevance
“…Studies have used a range of exercise modalities, with cycling the most common mode employed (Yamamoto et al, 1991; Radaelli et al, 1996; Tulppo et al, 1996, 1998; Hautala et al, 2003; Casties et al, 2006; Cottin et al, 2006; Karapetian et al, 2008; Martinmaki and Rusko, 2008; Martinmaki et al, 2008), although walking/running has also been utilized (Hautala et al, 2003; Cottin et al, 2007; Botek et al, 2010; Kaikkonen et al, 2010). Other modes less commonly used are arm-cranking (Tulppo et al, 1999; Leicht et al, 2008), rowing (Cheng et al, 2005) and swimming (Di Michele et al, 2012). Regarding the effect of exercise dose factors (intensity, duration, and modality), intensity has received the most investigative attention, while fewer studies have investigated the effects of duration and modality.…”
Section: Hrv During Exercisementioning
confidence: 99%
“…Studies have used a range of exercise modalities, with cycling the most common mode employed (Yamamoto et al, 1991; Radaelli et al, 1996; Tulppo et al, 1996, 1998; Hautala et al, 2003; Casties et al, 2006; Cottin et al, 2006; Karapetian et al, 2008; Martinmaki and Rusko, 2008; Martinmaki et al, 2008), although walking/running has also been utilized (Hautala et al, 2003; Cottin et al, 2007; Botek et al, 2010; Kaikkonen et al, 2010). Other modes less commonly used are arm-cranking (Tulppo et al, 1999; Leicht et al, 2008), rowing (Cheng et al, 2005) and swimming (Di Michele et al, 2012). Regarding the effect of exercise dose factors (intensity, duration, and modality), intensity has received the most investigative attention, while fewer studies have investigated the effects of duration and modality.…”
Section: Hrv During Exercisementioning
confidence: 99%
“…These variables were essential to determine the physical condition of these swimmers, and especially HR and RPE, were important in the verification of the state of the swimmers immediately before and after the tests 5,19 , in the verification of the longest distance incrementally swum by the swimmer in the PSwT 11 , and in the least amount of time in the simulated 400 MF test 1,23 . In the NLP and time needed to perform the test, significant differences were observed, as well as the inverse correlation between the two tests (Table 2), taking into account the fact that the mean time for the 400 MF test was larger than that of the PSwT, and the distance that the swimmers swum to reach VO2max in the PSwT had smaller mean values than those of the 400 MF.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, there is a trend to conduct research in order to evaluate the swimmers' cardiorespiratory fitness, and it is imperative that the choice of test is the closest possible to their sport reality. Thus, the design or adaptation of swimming tests require caution to meet the criteria of scientific authenticity, providing greater precision through their consistency (reproducibility), authenticity (validity), and association to real-life situations (applicability) 4,5 . There is a solid set of evidence that the 400 meters freestyle swimming test is closely related to the VO2max (ml/kg.min −1 ) of high-performance swimmers when evaluated in a laboratory setting 6 .…”
Section: Introductionmentioning
confidence: 99%
“…8 The high price of respiratory gas systems has prompted efforts to estimate the AT without respiratory gas analysis, with help from parameters such as the heart rate deflection point 9 and heart rate variability. 10 In 1982, Conconi et al discovered that the heart rate deflection point coincides with the lactate threshold. 11 Michele et al recently reported that the AT can be assessed by analyzing heart rate variability.…”
Section: Estimation Of Anaerobic Threshold a Classical Index Drawingmentioning
confidence: 99%
“…11 Michele et al recently reported that the AT can be assessed by analyzing heart rate variability. 10 In this issue of the Journal, Tanaka et al 12 also focus on the noninvasive detection of the lactate threshold without respiratory gas analysis. They draw attention to the amplitude of the first sound (AHS1) measured from a phonocardiogram.…”
Section: Estimation Of Anaerobic Threshold a Classical Index Drawingmentioning
confidence: 99%